Mutational analysis of the CAR1 UASI responsible for induced expression of the arginase gene in Saccharomyces cerevisiae - Fourie, Magdelena Gertruida (Stellenbosch : Stellenbosch University, 2012)
In the title the 'I' in 'UASI' is subscript.